2022
DOI: 10.1037/rev0000289
|View full text |Cite
|
Sign up to set email alerts
|

The cultural origins of symbolic number.

Abstract: In order to explain the unacceptability of certain long-distance dependencies --termed syntactic islands by Ross (1967) --syntacticians proposed constraints on long-distance dependencies which are universal and purely syntactic and thus not dependent on the meaning of the construction (Chomsky 1977(Chomsky , 2006. This predicts that these constraints should hold across constructions and languages. In this paper, we investigate the "subject island" constraint across constructions in English and French, a constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 202 publications
(360 reference statements)
0
14
0
Order By: Relevance
“…With instruction, human beings may also come to understand symbolic representations of number (O'Shaughnessy, Gibson, & Piantadosi, 2021). We count arrays of objects and we use numerical symbols such as Arabic digits to refer to precise quantities.…”
Section: Introductionmentioning
confidence: 99%
“…With instruction, human beings may also come to understand symbolic representations of number (O'Shaughnessy, Gibson, & Piantadosi, 2021). We count arrays of objects and we use numerical symbols such as Arabic digits to refer to precise quantities.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that none of the predictions were supported: Not all human groups have developed numbers and symbol systems vary widely across those that have (Chrisomalis, 2010), numbers are difficult for children to learn (Baroody, 2006), and timing of learning depends on external factors such as the amount of data that children are exposed to (Levine et al, 2010). O’Shaughnessy et al (2022) concluded that symbolic number systems have developed in response to social and economic needs of particular cultures, rather than innate or biological causes. For example, “modern” Hindu-Arabic numerals only became widely used in Europe after Leonardo of Pisa published Liber Abaci (“The Book of Calculation”) in 1202, which showed that algorithmic calculation with Hindu-Arabic numerals was superior to existing methods with Roman numerals and abacus and was very influential among Venetian merchants and traders (Sigler, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the historical development of mathematics has clearly been affected by economic and cultural factors, O’Shaughnessy et al’s (2022) proposal overlooks the universal features of symbolic number systems. Chrisomalis (2010) provided a structural typology of all known notation systems—over 100 different systems that have been used in the past 5,500 years—which associate “numeral phrases” (i.e., strings of symbols) with particular exact numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with this account: when there were discrepancies in performance across different versions of tasks, they tended to occur in formally educated children. There are other examples of practice and context influencing numerical ability including studies of market vs. school arithmetic in Brazilian [ 33 , 34 ] and Indian [ 35 ] children, and in anthropological analyses of the influences of economics and trade in numerical literacy [ 36 , 37 ]. Beyond context, different tasks may have different demands on domain-general cognitive load, or working memory.…”
Section: Discussionmentioning
confidence: 99%